2022
DOI: 10.3389/fmicb.2022.880993
|View full text |Cite
|
Sign up to set email alerts
|

Cannabigerol Effect on Streptococcus mutans Biofilms—A Computational Approach to Confocal Image Analysis

Abstract: Biofilms are complex bacterial structures in which bacterial cells thrive as a community. Many bacterial species, including pathogens, form biofilms of high complexity and adaptability to a wide range of environmental conditions. One example of these is Streptococcus mutans, a gram-positive bacterium that has been associated with caries. Cannabigerol, a non-psychoactive cannabinoid, has been shown to affect S. mutans biofilms. In order to better characterize the effect of cannabigerol on biofilms of S. mutans,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
3
0
3
Order By: Relevance
“…This assay was performed similarly to the method described in [ 71 ]. In brief, the S. aureus biofilms formed on day 5 at the bottom of a flat-bottom 12-well microplate (Corning, Incorporated, Kennebunk, ME, USA) were washed twice with PBS and stained with 3.3 µM SYTO 9 (Invitrogen, Life Technologies, Carlsbad, CA, USA) and 2 µg/mL propidium iodide (PI; Sigma, St. Louis, MO, USA) and kept in the dark at RT for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…This assay was performed similarly to the method described in [ 71 ]. In brief, the S. aureus biofilms formed on day 5 at the bottom of a flat-bottom 12-well microplate (Corning, Incorporated, Kennebunk, ME, USA) were washed twice with PBS and stained with 3.3 µM SYTO 9 (Invitrogen, Life Technologies, Carlsbad, CA, USA) and 2 µg/mL propidium iodide (PI; Sigma, St. Louis, MO, USA) and kept in the dark at RT for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Se hallaron 9 estudios, 2 de ellos fueron estudios clínicos, 1 de intervención 19 y 1 observacional 20 , 1 estudio in vivo sobre modelo de ratones C57Bl6 32 , los 6 restantes estudios exclusivamente in vitro, 3 sobre cultivos de Estreptococos mutans [43][44][45] y 3 sobre cultivo de placa dental de voluntarios 14,46,47 .…”
Section: Acción Antimicrobianaunclassified
“…Los estudios in vitro realizados sobre S. mutans testearon el adicionamiento de CBD y CBG en cultivo, observando alteración en la estructura y morfología bacteriana, así como una disminución de su actividad metabólica, los biofilms se presentaron más desorganizados y porosos, las UFC se redujeron, disminuyendo la densidad bacteriana [43][44][45] .…”
Section: Acción Antimicrobianaunclassified
“…Farha et al have shown that multiple cannabinoids employed at 2 µg/mL are potent inhibitors of S. aureus biofilm formation, with cannabigerol (CBG) at 4 µg/mL seemingly able to disperse preformed biofilms and rapidly kill persister cells [ 12 ]. CBD and CBG have also been shown to prevent biofilm formation by the related, cariogenic bacterium, Staphylococcus mutans UA159 [ 57 , 58 ].…”
Section: The Antimicrobial Properties Of Cannabis and Cannabis-derive...mentioning
confidence: 99%